The Return of Nature as an Operative Model: Decoding of Material Properties as Generative Inputs to the Form-Making Process. (June 2013) - Abondano, David
The abandonment of nature as an architectural model and the redefinition of the relationship between form and material were two of the main consequences of industrialization for modern architecture. While nature was replaced by the machine as a model for architecture, industrial production suppressed the craftsman's knowledge of the material and the associated techniques once essential to the form-making process. Thus, the replacement of nature as a model implied that principles once related to natural processes started to be seen as industrial values, i.e., the economy of means stopped being recognized as a quality related to natural form-making processes and became a demand of industrial production. Nowadays, material properties and nature are being reintroduced into architecture with the help of digital technologies; that is, the return of nature though computation. As a result, nature has become an operational model as opposed to the visual or iconic one it used to be; its inner qualities and processes are being decoded in order to inform the form-making process and foster innovative digital ornamentation.